FUS Mislocalization and Vulnerability to DNA Damage in ALS Patients Derived hiPSCs and Aging Motoneurons - Higelin, Julia; Demestre, Maria; Putz, Stefan; Delling, Jan P.; Jacob, Christian; Lutz, Anne-Kathrin; Bausinger, Julia; Huber, Anne-Kathrin; Klingenstein, Moritz; Barbi, Gotthold; Speit, Günter; Huebers, Annemarie; et al. (Frontiers in Cellular Neuroscience, 2016)
Mutations within the FUS gene (Fused in Sarcoma) are known to cause Amyotrophic Lateral Sclerosis (ALS), a neurodegenerative disease affecting upper and lower motoneurons. The FUS gene codes for a multifunctional RNA/DNA-binding protein that is primarily localized in the nucleus and is involved in cellular processes such as splicing, translation, mRNA transport and DNA damage response. In this study, we analyzed pathophysiological alterations associated with ALS related FUS mutations (mFUS) in human induced pluripotent stem cells (hiPSCs) and hiPSC derived motoneurons. To that end, we compared cells carrying a mild or severe mFUS in physiological- and/or stress conditions as well as after induced DNA damage. Following hyperosmolar stress or irradiation, mFUS hiPS cells recruited significantly more cytoplasmatic FUS into stress granules accompanied by impaired DNA-damage repair. In motoneurons wild-type FUS was localized in the nucleus but also deposited as small punctae within neurites. In motoneurons expressing mFUS the protein was additionally detected in the cytoplasm and a significantly increased number of large, densely packed FUS positive stress granules were seen along neurites. The amount of FUS mislocalization correlated positively with both the onset of the human disease (the earlier the onset the higher the FUS mislocalization) and the maturation status of the motoneurons. Moreover, even in non-stressed post-mitotic mFUS motoneurons clear signs of DNA-damage could be detected. In summary, we found that the susceptibility to cell stress was higher in mFUS hiPSCs and hiPSC derived motoneurons than in controls and the degree of FUS mislocalization correlated well with the clinical severity of the underlying ALS related FUS mutation. The accumulation of DNA damage and the cellular response to DNA damage stressors was more pronounced in post-mitotic mFUS motoneurons than in dividing hiPSCs suggesting that mFUS motoneurons accumulate foci of DNA damage, which in turn might be directly linked to neurodegeneration.